Policy framework for selecting medical tourism destinations: fuzzy- IPA approach - Heidary Dahooie, Jalil; Estiri, Mehrdad; Shahinpour, Sadaf (Anatolia : an international journal of tourism and hospitality research, 2024)
Using Fuzzy Importance-Performance Analysis (IPA) method, this study sought to develop a framework to identify and prioritize the factors influencing the selection of Iran by medical tourists. After a literature review, three main dimensions and 38 factors affecting tourism destination choices were identified. A Fuzzy SWARA questionnaire was used to ask experts how important each of the identified factors was to a medical tourist's choice of destination. In addition, medical tourists employed linguistic variables to assess the performance of the aforementioned factors. The results of the study revealed that "recommendations by friends and acquaintances," 'medical tourist's previous experiences, '"image/brand of the host country", "having friends or relatives in the destination country," and "international accreditation" were the top priorities for Iran's medical tourism policymakers and managers.